In Situ GWAS in Two Range‐Edge Populations of European Beech ( Fagus sylvatica L.) Identify Genetic Factors of Adaptation to Climate Change - Lauren Clément; Andrea Modica; Isabelle Lesur Kupin; Christophe Plomion; Catherine Bodénès; Grégoire Le Provost; Sylvie Oddou‐Muratorio; Katrin Heer; Marie Mirouze; Marie‐Christine Carpentier; Bartosz Ulaszewski; William Marande; et al. (Molecular Ecology, 2026)
In forest tree populations, the timing of budbreak (TBB) depends on several factors, both environmental and genetic. The genomic architecture underlying this trait is still not fully characterized. So far, common garden experiments have highlighted a few genomic regions with little heritability, while the whole spectrum of TBB variation observed in the wild still remains unexplored. We performed an in situ genome‐wide association study (GWAS) to investigate the genetic and environmental bases of phenotypic variation in budbreak in two wild range‐edge populations of the temperate continental tree, European beech ( Fagus sylvatica L.) surveyed in two consecutive years. We found distinct significant loci between populations and among years, suggesting that local adaptation has occurred and that genotype‐by‐environment interactions contribute to the observed variation. The phenotypic variance explained by the significant loci is between 0.2% and 54% for field data and 0% to 59% for modelled data, which suggests that while some traits are polygenic, some others are influenced by a few loci with large effects in the population, which demonstrates the relevance of conducting in situ GWAS in multiple populations. Our findings provide novel insights into the complex genetic architecture of TBB in forest trees. The genetic diversity of budbreak control provides opportunities for selection that could be used through assisted migration to help prepare beech forests to face climate change.

Genomic features and evolution of lifestyles support the recognition of distinct genera among fusarioid fungi - Bartosz Ulaszewski; Marcelo Sandoval-Denis; Johannes Z. Groenewald; Marileide M. Costa; Bagdevi Mishra; Sebastian Ploch; Pedro W. Crous; Marco Thines (Mycological Progress, 2025)
The family Nectriaceae ( Hypocreales , Sordariomycetes ) includes saprobes, endophytes and numerous important pathogens, several of which are of high commercial interest. Presently there are numerous genera scattered throughout the Nectriaceae that have a fusarioid asexual morph ( i.e. , genera with fusarium-like macroconidia). Fusarioid fungi encompass diverse lifestyles, including plant, human, and animal pathogens or associates, saprobes, lichenicolous species, endophytes, and mycophilic taxa. The fusarioid genera in Nectriaceae do not only differ in their sexual morphs, but also in their asexual morphology and biology, although their ecology has remained rather unclear. While genome data are available for numerous species, this has been mostly focused on Fusarium sensu stricto, as the genus encompasses most of the economically important species in this generic complex. To compliment this, we expanded the sampling, and generated whole genome sequences for 40 isolates representing the genera Atractium , Bisifusarium , Cinnamomeonectria , Corinectria , Cosmospora , Cyanonectria , Cylindrodendrum , Dialonectria , Fusarium , Fusicolla , Geejayessia , Ilyonectria , Macroconia , Macronectria , Microcera , Neocosmospora , Neonectria , Pseudofusicolla , Rectifusarium , Rugonectria , Scolecofusarium , Thelonectria , and Tumenectria . Phylogenomic ancestral reconstructions showed that plant pathogenicity is most likely ancestral to Fusarium and cylindrocarpioid genera, and revealed multiple and frequent lifestyle transitions. Although many species are prolific generalists, several genera appear to be more specialised, being primarily plant pathogens, mycophilic, or insect associated, while endophytism or plant pathogenicity evolved several times, and more recently in Fusarium. The broadly sampled Nectriaceae genomes supported morphological differences between most genera of Nectriaceae , mirrored by genome sizes, lactic enzymes, biosynthetic gene clusters, and small secreted proteins. Furthermore, it also supported a narrow circumscription of Fusarium in Nectriaceae that equals its morphology ( Gibberella sexual morphs), and biology.

Genome sequences for twenty-four Phytophthora and one Nothophytophthora species for the study of the evolution of pathogenicity in Peronosporaceae - Bartosz Ulaszewski; Bagdevi Mishra; Thomas Jung; Marco Thines (Mycological Progress, 2024)
Oomycetes classified in the genera Phytophthora and Nothophytophthora encompass a wide range of lifestyles, from saprotrophic and water-borne to destructive soil-borne or wind-dispersed plant pathogens. To clarify the evolutionary and genomic basis of these transitions, genome sequences for a wide range of species are necessary. However, the amount of genomes currently available is not representative of the full range of these lifestyles. To address this gap, we present draft genomes of 24 Phytophthora and one Nothophytophthora species, of which 14 have 100% BUSCO completeness for the Straminipila dataset. We hope that this resource will stimulate further research into the evolution of pathogenicity in Peronosporaceae .

Masting and Efficient Production of Seedlings: Balancing Costs of Variation Through Synchronised Fruiting - Michal Bogdziewicz; Igor Chybicki; Jakub Szymkowiak; Bartosz Ulaszewski; Jaroslaw Burczyk; Grażyna Szarek‐Łukaszewska; Katarzyna Meyza; Ewa Sztupecka; Mateusz Ledwoń; Łukasz Piechnik; Barbara Seget; Katarzyna Kondrat; et al. (Ecology Letters, 2024)
The efficient conversion of tissues into reproductive success is a crucial aspect affecting the evolution of life histories. Masting, the interannually variable and synchronous seed production in perennial plants, is a strategy that can enhance reproductive efficiency by mitigating seed predation and pollen limitation. However, evaluating benefits is insufficient to establish whether efficiency has improved, as such assessments neglect the associated costs of masting, particularly during the critical seed‐to‐seedling stage. We conducted a parentage analysis of seedlings and adults in a population of 209 Sorbus aucuparia trees, monitored over 23 years, providing pioneering documentation of the effects of masting on the fitness of individual trees beyond the seed stage. Our results show high costs of interannual variation that can be mitigated by high synchrony and reveal the existence of phenotypes that appear to reap the benefits of masting while avoiding its costs through regular reproduction.

Correction to: A novel synthesis of two decades of microsatellite studies on European beech reveals decreasing genetic diversity from glacial refugia - Camilla Stefanini; Katalin Csilléry; Bartosz Ulaszewski; Jarosław Burczyk; Michael E. Schaepman; Meredith C. Schuman (Tree Genetics & Genomes, 2023)

A novel synthesis of two decades of microsatellite studies on European beech reveals decreasing genetic diversity from glacial refugia - Camilla Stefanini; Katalin Csilléry; Bartosz Ulaszewski; Jarosław Burczyk; Michael E. Schaepman; Meredith C. Schuman (Tree Genetics & Genomes, 2023)
Genetic diversity influences the evolutionary potential of forest trees under changing environmental conditions, thus indirectly the ecosystem services that forests provide. European beech ( Fagus sylvatica L.) is a dominant European forest tree species that increasingly suffers from climate change-related die-back. Here, we conducted a systematic literature review of neutral genetic diversity in European beech and created a meta-data set of expected heterozygosity ( He ) from all past studies providing nuclear microsatellite data. We propose a novel approach, based on population genetic theory and a min–max scaling to make past studies comparable. Using a new microsatellite data set with unprecedented geographic coverage and various re-sampling schemes to mimic common sampling biases, we show the potential and limitations of the scaling approach. The scaled meta-dataset reveals the expected trend of decreasing genetic diversity from glacial refugia across the species range and also supports the hypothesis that different lineages met and admixed north of the European mountain ranges. As a result, we present a map of genetic diversity across the range of European beech which could help to identify seed source populations harboring greater diversity and guide sampling strategies for future genome-wide and functional investigations of genetic variation. Our approach illustrates how to combine information from several nuclear microsatellite data sets to describe patterns of genetic diversity extending beyond the geographic scale or mean number of loci used in each individual study, and thus is a proof-of-concept for synthesizing knowledge from existing studies also in other species.

Using reduced representation libraries sequencing methods to identify cpDNA polymorphisms in European beech (Fagus sylvatica L) - Joanna Meger; Bartosz Ulaszewski; Giovanni G. Vendramin; Jaroslaw Burczyk (Tree Genetics & Genomes, 2019)

The complete chloroplast genome sequence of wild service tree Sorbus torminalis (L.) Crantz - Bartosz Ulaszewski; Elzbieta Sandurska; Ewa Sztupecka; Jaroslaw Burczyk (Conservation Genetics Resources, 2017)